Os avistamentos de baleias jubartes no Espírito Santo, Brasil: relações materiais-e-simbólicas entre pesquisadores e animais não humanos - Takeuchi, Sophia Scardua Pereira (2021)
The rising presence of humpback whales (Megaptera novaeangliae) in the everyday life of the population of Espírito Santo, Brazil, has happened in different ways. The attention given to the species is mostly due to the media coverage, that report the incre